Online electrochemical impedance spectroscopy detection integrated with step-up converter for fuel cell electric vehicle. (8th January 2019) - Wang, Hanqing; Gaillard, Arnaud; Hissel, Daniel
Abstract: Declining reserves of the crude oil and increasingly serious environmental pollution have emphasized the requirement of a suitable substitute to our actual petroleum-based automobile market. An environmentally-friendly and efficient power generation device based on a sustainable energy source is attractive to settle this issue and realize cleaner production. Proton Exchange Membrane Fuel Cell (PEMFC), which achieves zero emission, modular construction, high energy conversion ratio and etc., has been treated as one of the most promising solution for automobile applications. Nevertheless, many technical restrictions such as relatively short life cycle have still to be conquered before satisfying the requirements of large-scale commercialization. Electrochemical Impedance Spectroscopy (EIS) is an effective technique for fault detection of electrochemical system. This paper presents an on-line EIS detection strategy based on the proposed fuel cell stack connected step-up converter. No additional equipment is required compared with conventional detection process. Furthermore, the proposed 6-phase Interleaved Boost Converter (IBC) based on Silicon Carbide (SiC) semiconductors and inverse coupled inductors has achieved low input current ripple, high efficiency, high voltage gain ratio, high compactness and high redundancy. Benefiting from these advantages, the lifespan of fuel cell stack can be extended. The proposed online EIS detection has been realized and the results have been compared with theoretical analysis. Highlights: A six-phase interleaved boost converter based on silicon carbide semiconductor and inverse coupled inductor was proposed. Online electrochemical impedance spectroscopy detection functionality was integrated with Sliding-Mode Control strategy. Close loop control was realized even during the impedance detection processes. The frequency range of impedance was from 1 Hz to 10 kHz. The simulation results matched well with the theoretical results.